1986
DOI: 10.1111/j.1745-3984.1986.tb00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Processing Strategies and the Construct Validity of Verbal Reasoning Tests

Abstract: This study examines the influence of processing strategies, and the associated metacomponents that determine when to apply them, on the construct validity of a verbal reasoning test. Three strategies for solving verbal analogy items were examined: a rule-oriented strategy, an association strategy, and a partial rule strategy. Construct validity was studied in two separate stages: construct representation and nomothetic span. For construct representation, evidence was obtained that all three strategies, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…First, item properties are often predicted at least moderately well. Studies from my laboratory have concerned ten different item types, including verbal analogies and verbal classifications (Embretson, 1984;Embretson, 1985;Embretson & Schneider, 1989;Embretson, Schneider & Roth, 1985;Whitely, 19801), geometric analogies and geometric classifications (Whitely & Schneider, 1981), series completion (Embretson, 1985), paragraph comprehension (Embretson & Wetzel, 1987), spatial folding (Embretson, 1991(Embretson, , 1994, mathematics word problems (Embretson, 1995a), matrix completion problems (Embretson, 1995c; and, most recently, spatial construction items. Prediction levels comparable to a multiple correlation of at least .70 are usually obtained.…”
Section: Advantagesmentioning
confidence: 99%
“…First, item properties are often predicted at least moderately well. Studies from my laboratory have concerned ten different item types, including verbal analogies and verbal classifications (Embretson, 1984;Embretson, 1985;Embretson & Schneider, 1989;Embretson, Schneider & Roth, 1985;Whitely, 19801), geometric analogies and geometric classifications (Whitely & Schneider, 1981), series completion (Embretson, 1985), paragraph comprehension (Embretson & Wetzel, 1987), spatial folding (Embretson, 1991(Embretson, , 1994, mathematics word problems (Embretson, 1995a), matrix completion problems (Embretson, 1995c; and, most recently, spatial construction items. Prediction levels comparable to a multiple correlation of at least .70 are usually obtained.…”
Section: Advantagesmentioning
confidence: 99%
“…Nor can the criticism be countered by pointing to the large amount of correlation data Norris Background Beliefs and Critical Thinking Testing -5 relating performance on the Watson-Glaser test to other variables (Watson & Glaser, 1980b). This data provides evidence on the convergent and discriminant validity of the test, but it is not compelling when the same data used to elaborate the nomothetic span of a test is also used to clarify the construct the test measures in the first place (Embretson, Schneider, & Roth, 1986). This is especially true for the construct of critical thinking.…”
Section: The Watson-glaser Critical Thinking Appraisalmentioning
confidence: 96%
“…The second limitation is that measures of general cognitive ability focus on the outcome of performance and overlook important process elements of performance, such as problem-solving approaches (Embretson, Schneider, & Roth, 1986;Sigel, 1963). hi support of the difference between general cognitive ability and problem solving processes, several studies have found that measures of general intelligence tend to have low correlations with real-life problem-solving performance (Epstein & Meier, 1989;Heppner & et al, 1982;Spivak, Shure, & Platt, 1985;Stemberg, Wagner, Williams, & Horvath, 1995).…”
Section: General Cognitive Abilitymentioning
confidence: 99%